2019
DOI: 10.1201/9780367853167
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Human Interventions on the Hydrology of Nile Basin Headwaters, the Case of Upper Tekeze Catchments

Abstract: This research was conducted under the auspices of the Graduate School for SocioEconomic and Natural Sciences of the Environment (SENSE) CRC Press/Balkema is an imprint of the Taylor & Francis Group, an informa business

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 182 publications
(522 reference statements)
0
12
0
Order By: Relevance
“…A combination of human activities including land use/cover change, water abstraction and SWC can modify the low flow of a catchment (Chang et al, ; Li et al, ). SWC activities can cause visible changes in the dry season flow regimes (Gebremicael, ; Mu et al, ; Wang et al, ). Large scale implementations of such interventions can modify the hydrological processes of a catchment by changing the partitioning of the incoming rainfall at the land surface (Gates et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of human activities including land use/cover change, water abstraction and SWC can modify the low flow of a catchment (Chang et al, ; Li et al, ). SWC activities can cause visible changes in the dry season flow regimes (Gebremicael, ; Mu et al, ; Wang et al, ). Large scale implementations of such interventions can modify the hydrological processes of a catchment by changing the partitioning of the incoming rainfall at the land surface (Gates et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Ghba River subbasin is one of the Nile River's principal tributaries. The landscape include hills and highlands in the north and northeast, as well as highlands in the center of the watershed [45,46]. Several rivers cut through the middle highlands before joining the major Tekeze River near Chemey in the southwest [47].…”
Section: Description Of the Study Subbasinmentioning
confidence: 99%
“…Furthermore, the SAI result showed that most of the years exhibited negative anomalies in discharge, indicating a drier period. Moreover, a lot of large and small-scale irrigation schemes are found in Ghba subbasin [86,87], especially in the Agulai and Genfel catchments, which could be directly affected by low water availability during short rainy (MAM). e occurrence of high streamflow variability combined with the expansion of irrigation in the subbasin influences agriculture and crop productivity, which aggravates the prevalence of food insecurity and drought in the subbasin.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%